2018
DOI: 10.1177/0011128718770686
|View full text |Cite
|
Sign up to set email alerts
|

Target Congruence as a Means of Understanding Risk of Intimate Partner Violence: A Comparison of Male and Female College Students in the United States

Abstract: This study examines the effects of routine activities and target congruence—or the extent to which an individual’s characteristics match up with offenders’ needs, motives, or reactivities—on intimate partner violence. We also examine whether the effect of target congruence is moderated by gender. Using a nationwide sample of more than 74,000 students from 129 universities across the United States, the results show that indicators of target antagonism, target gratifiability, and target vulnerability are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…Furthermore, consistent with research on pathways theory (Gehring, 2018; McClellan et al, 1997; Salisbury & Van Voorhis, 2009; Simons & Whitbeck, 1991; Watts & Iratzoqui, 2019; Widom & White, 1997), some turning points had different relationships with the nature of co-offending depending upon gender, providing partial support for Hypothesis 6. This is consistent with a great deal of work on the gendered nature of risk factors for outcomes such as crime (Belknap & Holsinger, 2006; Holtfreter et al, 2004; Reisig et al, 2006; Van Voorhis et al, 2010; Walters, 2018; Zimmerman & Messner, 2010) and victimization (Elvey & McNeeley, 2018; Wilcox et al, 2009). However, although there was evidence that the predictors of co-offending are somewhat gendered, the results were not entirely consistent with pathways theory.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, consistent with research on pathways theory (Gehring, 2018; McClellan et al, 1997; Salisbury & Van Voorhis, 2009; Simons & Whitbeck, 1991; Watts & Iratzoqui, 2019; Widom & White, 1997), some turning points had different relationships with the nature of co-offending depending upon gender, providing partial support for Hypothesis 6. This is consistent with a great deal of work on the gendered nature of risk factors for outcomes such as crime (Belknap & Holsinger, 2006; Holtfreter et al, 2004; Reisig et al, 2006; Van Voorhis et al, 2010; Walters, 2018; Zimmerman & Messner, 2010) and victimization (Elvey & McNeeley, 2018; Wilcox et al, 2009). However, although there was evidence that the predictors of co-offending are somewhat gendered, the results were not entirely consistent with pathways theory.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, the pathways literature suggests that the turning points identified in Hypothesis 5 are especially salient for female crime (McClellan et al, 1997; Salisbury & Van Voorhis, 2009; Simons & Whitbeck, 1991). However, because male and female victimization may be influenced by different risk factors (e.g., Elvey & McNeeley, 2018; Wilcox, Tillyer, & Fisher, 2009), the consequences of child abuse and victimization may differ by gender as well. Consistent with this idea, studies confirm that the effects of child maltreatment on delinquency vary by gender (Watts & Iratzoqui, 2019; Widom & White, 1997).…”
Section: Gender Pathways and Co-offendingmentioning
confidence: 99%
“…A student’s living situation can also influence an individual’s physical proximity to motivated offenders. While previous research has operationalized this concept as whether the respondent lives on campus (Elvey & McNeeley, 2019; Snyder, 2015), it is likely more important to scrutinize who the respondent lives with . As Elvey and McNeeley (2019) suggested, respondents who live on campus likely do not live with romantic partners, which is important to assessing victimization risk given the ubiquity of intimate partner SA (Tjaden & Thoennes, 2006).…”
Section: Theorizing Routine Activities In the Context Of Campus Sexual Victimizationmentioning
confidence: 99%
“…While previous research has operationalized this concept as whether the respondent lives on campus (Elvey & McNeeley, 2019; Snyder, 2015), it is likely more important to scrutinize who the respondent lives with . As Elvey and McNeeley (2019) suggested, respondents who live on campus likely do not live with romantic partners, which is important to assessing victimization risk given the ubiquity of intimate partner SA (Tjaden & Thoennes, 2006). Moreover, Schreck and Fisher (2004) posit that individuals who live with family will have a reduced likelihood of being in physical proximity with motivated offenders resulting in a reduced likelihood of victimization.…”
Section: Theorizing Routine Activities In the Context Of Campus Sexual Victimizationmentioning
confidence: 99%
“…It is also important to mention, especially for the research topic analyzed here, the research carried out by Kalof [21] in which it is suggested that many victims of gender-based violence in the academic environment do not perceive GBV as such, in addition to the existing relationship among the structures that reinforce a model of masculinity in which some men may have assumed. Several current studies in this field have made it possible to examine in greater depth the university as a social space that also has to deal with gender-based violence and that has special characteristics that need to be analyzed to understand the complexity of this social problem [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%